Functional insights to the development of bioactive material for combating bacterial infections - Fan, Duoyang; Liu, Xiaohui; Ren, Yueming; Bai, Shuaige; Li, Yanbing; Luo, Ziheng; Dong, Jie; Chen, Fei; Zeng, Wenbin (Frontiers in Bioengineering and Biotechnology, 2023)
The emergence of antibiotic-resistant "superbugs" poses a serious threat to human health. Nanomaterials and cationic polymers have shown unprecedented advantages as effective antimicrobial therapies due to their flexibility and ability to interact with biological macromolecules. They can incorporate a variety of antimicrobial substances, achieving multifunctional effects without easily developing drug resistance. Herein, this article discusses recent advances in cationic polymers and nano-antibacterial materials, including material options, fabrication techniques, structural characteristics, and activity performance, with a focus on their fundamental active elements.